DOI: 10.31274/rtd-180813-12599
|View full text |Cite
|
Sign up to set email alerts
|

Strip position, tillage, and water regime effects on a strip intercropping rotation

Abstract: ACKNOWLEDGEMENTS 125 position on crop yields; and 2) to determine the effect of tillage, strip position, and their interaction, on soil water content during the season, and its relationship with crop yields. Explanation of Dissertation. The dissertation is presented in three sections, each a manuscript to be submitted to the scientific journals of the American Society Agronomy, the last two as related papers. The first section, entitled "Strip intercropping rotation of corn (Zea mays L.), soybeans (Glycine max… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…However, SB com also yielded more than com in the other treatments at NERC in 1989. There may have been differential soil moisture use by the crops into which com was rotated in 1989, a phenomenon reported by Garcia-Prdchac (1991).…”
Section: Corn Yieldsmentioning
confidence: 98%
See 1 more Smart Citation
“…However, SB com also yielded more than com in the other treatments at NERC in 1989. There may have been differential soil moisture use by the crops into which com was rotated in 1989, a phenomenon reported by Garcia-Prdchac (1991).…”
Section: Corn Yieldsmentioning
confidence: 98%
“…Competition for moisture between crops plays a large part in determining which crop strips over-yield and which suffer yield reductions. In dry years (Cmse, 1990;Garcia-Prdchac, 1991;Fortin et al, 1994;Choromanska, 1995) or without irrigation (Lesoing and Francis, 1990) this competition can flatten or reverse the overyielding often seen in border rows of com. Garcia et al (1990) found that tillage type affected strip intercrop performance through its effect on soil water, particularly in a dry year.…”
Section: Border Effectsmentioning
confidence: 99%
“…Competition for water is a very serious problem in semi-arid environments (Hulbert and Remsberg, 1927). Garcia-Prechac (1991) reported that corn grown next to oat can experience yields reductions under dry conditions and yield increases under wet or normal conditions compared to strip center yields. Moisture effects on border yield was also analyzed by Fortin et al (1994).…”
Section: Natural Resource Use In Strip Intercroppingmentioning
confidence: 99%